Phenological Performance, Thermal Demand, and Qualitative Potential of Wine Grape Cultivars Under Double Pruning - Carolina Ragoni Maniero; Marco Antonio Tecchio; Harleson Sidney Almeida Monteiro; Camilo André Pereira Contreras Sánchez; Giuliano Elias Pereira; Juliane Barreto de Oliveira; Sinara de Nazaré Santana Brito; Francisco José Domingues Neto; Sarita Leonel; Marcelo de Souza Silva; Ricardo Figueira; Pricila Veiga dos Santos (Agriculture)
The production of winter wines in Southeastern Brazil represents a relatively recent but expanding viticultural approach, with increasing adoption across diverse wine-growing regions. This system relies on the double-pruning technique, which allows for the harvest of grapes during the dry and cooler winter season, favoring a greater accumulation of sugars, acids, and phenolic compounds. This study aimed to characterize the phenological stages, thermal requirements, yield, and fruit quality of the fine wine grape cultivars ‘Sauvignon Blanc’, ‘Merlot’, ‘Tannat’, ‘Pinot Noir’, ‘Malbec’, and ‘Cabernet Sauvignon’ under double-pruning management in a subtropical climate. The vineyard was established in 2020, and two production cycles were evaluated (2022/2023 and 2023/2024). Significant differences in the duration of phenological stages were observed among cultivars, ranging from 146 to 172 days from pruning to harvest. The accumulated thermal demand was higher in the first cycle, with a mean of 1476.9 growing degree days (GDD) across cultivars. The results demonstrate the potential of Vitis vinifera L. cultivars managed with double pruning for high-quality wine production under subtropical conditions, supporting the viability of expanding viticulture in the state of São Paulo. ‘Cabernet Sauvignon’ and ‘Sauvignon Blanc’ showed the highest yields, reaching 3.03 and 2.75 kg per plant, respectively, with productivity values of up to 10.8 t ha−1. ‘Tannat’ stood out for its high sugar accumulation (23.4 °Brix), while ‘Merlot’ exhibited the highest phenolic (234.9 mg 100 g−1) and flavonoid (15.3 mg 100 g−1) contents. These results highlight the enological potential of the evaluated cultivars and confirm the efficiency of the double-pruning system in improving grape composition and wine quality in non-traditional viticultural regions.